A necessidade de uma leitura contemporânea e analítica do Princípio Regulador do Culto - Prado, Renato Marinoni dos Santos (2019)
The growth of the reformed faith from the second decade of the twenty-first century and the challenges to the Christian faith brought by post-modernity have reignited the debate on a christian service that is biblical but at the same time relevant and that dialogue with the culture. This research aims to contribute to this debate by first recovering the pedagogical role of the collective meeting of christian worship in the formation of the christian character in the life of the worshiper, through the importance of liturgical practice and rituals in this process. Then we will look at the Reformers' understanding and the central importance they all gave to christian worship in reinforcing Reformed ideals and how they designed the services in their contexts. Given this, we will see John Calvin's understanding of christian worship more closely, since Calvin was the greatest influence on the Protestant branch called Reformed Theology. It was within the Reformed faith of the Calvinist context that arose, some time later, this concern for the necessity of formulating some principles for the reformed service. This initiative, which took place in England in a context of denominational diversity but dominated by Puritans and Anglicans, gave rise to the "Westminster Directory of Worship," which brings the formulation of what would come to be known in history as "Regulative Principle of Worship, which is, in short, the application of the Sola Scriptura principle to what should or should not happen in christian worship. We will look at the context in which the initial formulation of the "Regulative Principle of Worship" was given, whether if there really is an alignment between this principle and the Scriptural view of congregational worship and how it came to be applied in the history after its formulation. In the last chapter, we will examine contemporary liturgical proposals and investigate the hypothesis that if the Regulative Principle of Worship truly delineates, according to the Scriptures, what is proper or not for a christian worship, according to the ordinances and revelation of God himself, it should be applied to all aesthetic styles of worship, just as the Gospel can and should be preached in all times and cultures